2014
DOI: 10.1016/j.neuron.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Is Required for Optimal Waiting Based on Decision Confidence

Abstract: SUMMARY Confidence judgments are a central example of metacognition—knowledge about one’s own cognitive processes. According to this metacognitive view, confidence reports are generated by a second-order monitoring process based on the quality of internal representations about beliefs. Although neural correlates of decision confidence have been recently identified in humans and other animals, it is not well understood whether there are brain areas specifically important for confidence monitoring. To address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
294
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(338 citation statements)
references
References 66 publications
(130 reference statements)
37
294
6
1
Order By: Relevance
“…In support of this theoretical work, pulvinar neurons have been shown to encode confidence, a second order variable, independently of other areas processing first order variables; this study thus suggested that one population of neurons can read-out neural population that encode primary sensory variables (Komura et al, 2013). Other studies have also suggested that particular brain regions independently code for first and second order signals (Lak et al, 2014). In line with these ideas, the mapping between β power and duration interval may be realized via networking through higher order brain regions.…”
Section: Markers Of Metacognitive Inference As Internal State Variablsupporting
confidence: 63%
“…In support of this theoretical work, pulvinar neurons have been shown to encode confidence, a second order variable, independently of other areas processing first order variables; this study thus suggested that one population of neurons can read-out neural population that encode primary sensory variables (Komura et al, 2013). Other studies have also suggested that particular brain regions independently code for first and second order signals (Lak et al, 2014). In line with these ideas, the mapping between β power and duration interval may be realized via networking through higher order brain regions.…”
Section: Markers Of Metacognitive Inference As Internal State Variablsupporting
confidence: 63%
“…In waiting-time paradigms, reward is delivered for correct decisions, but only after a delay and the subject has the opportunity to initiate a new trial instead of waiting. Waiting after an error thus has an opportunity cost, so willingness to wait should, normatively, depend on the estimated accuracy (Kepecs et al, 2008;Lak et al, 2014). For more examples and details on paradigms, see Kepecs and Mainen (2012) and for a review of comparative studies, see Smith et al (2003).…”
Section: Decision Optimizationmentioning
confidence: 99%
“…Finally, interoceptive awareness has been associated with the ACC, IC, prefrontal cortex (PFC, Brodmann area 10 (BA10) [26,27]) and OFC [28,29]. Although this metacognitive dimension has not been examined in neurological populations, impaired awareness and diminished insight are core features of dementia [30,31].…”
Section: Introductionmentioning
confidence: 99%